PENGGUNAAN E-MONEY TERHADAP PERILAKU KONSUMTIF MAHASISWA YANG DIMEDIASI KONTROL DIRI - Luh Gede Kusuma Dewi; Nyoman Trisna Herawati; I Made Pradana Adiputra (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
This study aims to analyze the effect of e-money on the consumptive behavior of undergraduate accounting students in Bali Province which is mediated by self-control. This study uses a quantitative research design with an ex post facto approach and path analysis techniques. The data of this research were collected by distributing questionnaires openly using google form media to all universities in Bali. The study population was S1 Accounting students at all universities in Bali Province. The sample was selected using purposive random sampling technique. The total sample of the study was 354 people. The results showed that e-money and self-control had a direct effect on consumptive behavior. In addition, the results of the study also showed that self-control was able to mediate the relationship between e-money and consumptive behavior. This shows that it is important to improve self-control to form good financial behavior among accounting students.